2016
DOI: 10.1007/jhep02(2016)114
|View full text |Cite
|
Sign up to set email alerts
|

Solid holography and massive gravity

Abstract: Momentum dissipation is an important ingredient in condensed matter physics that requires a translation breaking sector. In the bottom-up gauge/gravity duality, this implies that the gravity dual is massive. We start here a systematic analysis of holographic massive gravity (HMG) theories, which admit field theory dual interpretations and which, therefore, might store interesting condensed matter applications. We show that there are many phases of HMG that are fully consistent effective field theories and whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
214
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(228 citation statements)
references
References 103 publications
14
214
0
Order By: Relevance
“…Only very recently a proposal has appeared for the gravitational dual of elasticity in terms of the "Stueckelberg star" [215]. This is in a boundary language which is closely related to the language we have been using.…”
mentioning
confidence: 70%
“…Only very recently a proposal has appeared for the gravitational dual of elasticity in terms of the "Stueckelberg star" [215]. This is in a boundary language which is closely related to the language we have been using.…”
mentioning
confidence: 70%
“…where 20) and c d and c d are numerical factors, one can easily find that the entanglement entropy in this limit reads…”
Section: Jhep10(2016)135mentioning
confidence: 99%
“…Breaking the translational symmetry itself can be done within different mechanisms. This is studied either by considering impurities in the system [10][11][12], breaking the diffeomorphism invariance in the bulk theory [13][14][15], turning on spatial dependent sources [16][17][18][19][20][21] or considering backreacted geometries from probe charged matter [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…We found that Ω Gm 2 Ξ, where Ξ ≡ ξ /(K + G) is defined from the bulk and shear moduli K, G and the longitudinal phonon diffusivity ξ . 56 In other words, the ratio Ω/m 2 , where both quantities depend on the microscopic details of the system and of the breaking of translations, is given by universal thermodynamic and hydrodynamic data.…”
Section: Introductionmentioning
confidence: 99%